The Relationship between Second Language Acquisition Process and English Language Teaching in Indonesia - Pritz Hutabarat (Journal of English Language Teaching and Linguistics, 2016)
English as a global language is learned worldwide and a plethora of methods and approaches have been developed and practiced in English classrooms by dedicated teachers and students. Understanding the underlying theories of second and foreign language acquisition and learning will help both teachers and students in learning and teaching a target language. There has not been many research conducted in the area, especially within Indonesian context. This research therefore attempts to fill in gaps in a way that it provides sufficient discussion of the theories and practice in English Language Teaching (ELT) in Indonesia in its conjunction with the second and foreign language acquisition theories. Twenty eight students specializing in teacher training participated in the research and two distinguished data collection methods were utilized; survey and interview. The results show that the students are not consistent with their opinions concerning the theories of second or foreign language acquisition and learning in relation to the mastery of English as a foreign language in Indonesia. Keywords: language learning, language acquisition, ELT